Hematological Parameters in Adult Type 2 Diabetes Mellitus Patients Visiting a Tertiary Care Center of Western Nepal - Prajapati, Saraswoti; Mishra, Satyendra Kumar; Pokhrel, Buddhi Raj Pokhrel; Shah, Anita; Shrestha, Jharana; Gharti, Sakar Babu (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Various mechanisms suggest changes in hematological proﬁles of Type 2 Diabetes Mellitus (T2DM) patients. Similarly, alterations in hematological proﬁles have been linked with pathogenic mechanisms in Diabetes. We aim to determine hematological proﬁles of adult MATERIAL AND METHODS This hospital-based cross-sectional study was conducted from March 2020 to December 2020 at the department of Pathology and Biochemistry of Universal College of Medical Sciences. After ethical clearance (UCMS/IRC/016/20), 90 adult patients diagnosed with T2DM were considered. Both verbal and written consent was taken. Type 1 diabetics, patients with history of hemoglobinopathies, recent blood transfusion, chronic illnesses and acute infections, and whose peripheral smear showed dimorphic pictures were excluded. The glycemic and hematological parameters were estimated. The data were analyzed using SPSS (version 20). Categorical data were expressed in frequency and percentage. Numerical data were expressed as median (interquartile range). Mann-Whitney U test was used to compare the hematological parameters between patients with good and poor glycemic control. RESULTS Among the total 90 participants, 34.4% had anemia. Mean Corpuscular Hemoglobin Concentration (MCHC) correlated positively with both Random Blood Sugar (RBS) and HbA1C. RBC count and Packed Cell Volume (PCV) were signiﬁcantly higher in patients with good glycemic control, whereas MCHC was signiﬁcantly lower in that group. CONCLUSION High prevalence of anemia was noted in T2DM patients. RBC and PCV levels were signiﬁcantly lower in patients with poor glycemic control and MCHC levels were signiﬁcantly lower in patients with good glycemic control.